Hubungan Perilaku Bullying Dengan Harga Diri Remaja Di SMP N 2 Langowan Kabupaten Minahasa - Poli, Jeremia Sefanya; Bidjuni, Hendro; Simak, Valen Fridolin (Mapalus Nursing Science Journal, 2023)
Abstract   Backround bullying is behavior aggressive form abuse power exercised by a person / group to others, so could resulted damage physical , psychological and social in a manner repeated , which is often happened at school. Purpose For analyze Connection Behavior bullying With Self Respect teenagers at Middle School 2 Langowan. Method Study this is study quantitative using a purposeful analytical survey for analyze connection Among two variable . With design cross sectional research and use questionnaire bullying behavior and prices self. Sample study consists of 145 teenage students with use random technique through method lottery . Univariate analysis use distribution frequency and analysis bivariate using the chi square test with level 95% significance (α=0.05). Result Based on results study connection behavior bullying with price self show that ie score p-value = 0.222. Discussion The discussion on the research is about the relationship between the relationship between bullying behavior and adolescent self-esteem at SMP N 2 Langowan. Conclucion Based on results research that has conducted that there is no connection significant between behavior bullying with Adolescent Self-Esteem at Middle School 2 Langowan. Keywords: Adolescent Self-Esteem; Bullying Behavior; School.